Interruption Practice Reduces Procedural Errors at the Post-Completion Step. (September 2014) - Zish, Kevin; Trafton, J. Gregory
Mitigating the effects of interruptions is important for tackling the increasing number of possible disruptions at home, at work, and online. Previous work has shown that the benefits of practice can decrease the amount of time it takes to resume a task after an interruption. This paper demonstrates that the same benefit can be extended to error rates at the post-completion step in a simulated computerized physician order entry (CPOE) system. This example of a real-world procedural task demonstrates that a general increase in interruptions leads to changes in performance for the final step of the task.